Genes Involved in Stress Response and Especially in Phytoalexin Biosynthesis Are Upregulated in Four Malus Genotypes in Response to Apple Replant Disease - Reim, Stefanie; Rohr, Annmarie-Deetja; Winkelmann, Traud; Weiß, Stefan; Liu, Benye; Beerhues, Ludger; Schmitz, Michaela; Hanke, Magda-Viola; Flachowsky, Henryk (Frontiers in Plant Science, 2020)
Apple replant disease (ARD) is a soil-borne disease, which is of particular importance for fruit tree nurseries and fruit growers. The disease manifests by a poor vegetative development, stunted growth and reduced yield in terms of quantity and quality, if apple plants (usually rootstocks) are replanted several times at the same site. Genotype-specific differences in the reaction of apple plants to ARD are documented, but less is known about the genetic mechanisms behind this symptomatology. Recent transcriptome analyses resulted in a number of candidate genes possibly involved in the plant response. In the present study, the expression of 108 selected candidate genes was investigated in root and leaf tissue of four different apple genotypes grown in untreated ARD soil and ARD soil disinfected by γ-irradiation originating from two different sites in Germany. Thirty-nine out of the 108 candidate genes were differentially expressed in roots by taking a p-value of < 0.05 and a fold change of > 1.5 as cutoff. Sixteen genes were more than 4.5-fold upregulated in roots of plants grown in ARD soil. The four genes MNL2 (putative mannosidase); ALF5 (multi antimicrobial extrusion protein); UGT73B4 (UDP-glycosyltransferase 73B4) and ECHI (chitin-binding) were significantly upregulated in roots. These genes seem to be related to the host plant response to ARD, although they have never been described in this context before. Six of the highly upregulated genes belong to the phytoalexin biosynthesis pathway. Their genotype-specific gene expression pattern was consistent with the phytoalexin content measured in roots. The biphenyl synthase (BIS) genes were found to be useful as early biomarkers for ARD, because their expression pattern correlated well with the phenotypic reaction of the Malus genotypes investigated.